Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency